Phylogenetic relationships of Argentinean Creole with other Latin American Creole Cattle as revealed by a medium density SNP microarray - Raschia, Maria Agustina; Poli, Mario Andres (Asociación Latinoamericana de Producción Animal, 2021)
The demographic history of the Criollo cattle in Argentina and in Latin America in general dates back to the time of Spanish colonization. The objective of this study was to investigate the potential use of a medium-density SNP microarray to describe animals from the most representative and oldest herds at the time the Argentine Association of Criollo Bovine Cattle Breeders was established and to explore the phylogenetic relationship with other Creole cattle from Latin America. With the genotypes of 51 animals in 34,008 autosomal SNPs, matrices of genetic distances were generated based on the proportion of identical alleles by state shared between animals and between animals grouped according to their origin, with the PLINK program. A phylogenetic tree based on genetic distances between pairs of animals was constructed using PHYLIP, and prepared for visualization with FigTree. A multidimensional scaling analysis was performed to evaluate the relationship in terms of genetic distance between the different groups of animals. The genetic distances between animals ranged from 0.186 to 0.357 when considering all pairs of animals, and from 0.186 to 0.338 when considering pairs of creoles. The dendrogram obtained presented three clusters. Group 1 included Creole cattle from Colombia, Guadalupe, Paraguay and Uruguay, and the reference groups Holando and Jersey. Group 2 comprised exclusively Patagonian Creole cattle, while the third group included the remaining Argentine Creoles. The genetic relationship patterns obtained through multidimensional scaling demonstrated an intimate relationship between criollos of four origins in Argentina. This can be explained in part by the early migration of animals that originated the founding herds in some Argentine localities. The results of this study will contribute to a better understanding of the formation of the founding herds of criollos in Argentina and of the relationship with other populations of creole cattle in Latin America.